PENDIDIKAN AKHLAK DALAM POLA ASUH ORANG TUA - Hasnawati, Hasnawati (Jurnal Pendidikan Islam, 2016)
This paper intends to study the pattern of parenting is based on the perspective of Islamic education, especially moral education. However, all have an impact on the parenting behavior of children who care. Because there is a tendency that it affects all the parenting to intervention by the messages morals, manners, character, attitude and a certain character. In the perspective of moral education/Islam, all parenting basically to intervention by the attitude; 1 ) love, 2) love to pray; 3) gratitude; 4) fond of charity; 5) happy to share happiness with others; 6) always honest in saying or doing (do not lie to others); 7) adherence to the teachings of the religion/God; 8) to be firm yet polite and civilized; 9) always make use of leisure time were significantly; and 10) always pay attention to the rights of people alongside another patient in carrying out any form of liability /regulations set him. The ten akhlakiah dimension is reflected in parenting Muhammad Rasul while educating children, grandchildren and the whole community.